Recent Advances in Carbon-based Polymer Composites for Effective Electromagnetic Interference (EMI) Shielding - B H S Thimmappa, Aravind Karthik, Shivamurthy B, Nithesh Naik, Smarth Sharma, Dasharathraj K Shetty (International Journal of Advanced Science and Technology, 2020)
The aviation industry has been making excessive use of composite materials in the recent past.  It is essential to minimize aircraft weight by innovative materials and to provide desirable mechanical properties without affecting the distance for electromagnetic safety. This review describes the state of existing literature for various materials and manufacturing methods of carbon-based polymer composites used in electromagnetic interference (EMI) shielding. It provides an insight into the different methods of preparation of various EMI shielding materials and their efficiency in terms of attenuation of the EMI. The review also analyzes different methods to enhance EMI shielding effectiveness, various developments in the fabrication of efficient, lightweight composite materials with functional shielding capacity. A detailed literature review was conducted to identify all potentially relevant studies using the Springer®, Scopus®, and Web of Science®. Various research articles on fabrication and characterization of carbon-based composites to enhance the shielding effectiveness are considered and reviewed in the article. Most of the considered design here is composed of conductive carbon nanotubes infused with polymeric composite or metal-based composites. The scope of this review article is limited to only carbon-based composite materials.